The japanese economy - Flath, David (New York : Oxford University Press, 2022)
"This book is for anyone broadly interested in Japan, for it is impossible to fully understand Japan without learning what basic economics has to say about it, which is much. To know Japan-or any country for that matter-is more than an ability to recite a litany of facts about its history, geography, institutions, and culture. Disciplined thinking is needed to organize the disparate facts into a coherent system that can be grasped whole. Modern economics is the academic discipline underlying this book"--
Includes bibliographical references and index.
AAL
Keywords: Japan -- Economic conditions; Japan -- Economic policy